Статистична модель систем ідентифікації повітряних об’єктів - Свид, І. В.; Головатенко, С. В. (ХНУРЕ, 2023)
A significant role in the information support of the airspace control and air traffic control system is played by radar systems for identifying detected objects by the sign of “friend or foe”. In the presented work, a statistical model of identification systems for the evaluation of "friend or foe" is considered. And the influence of unintentional and intentional interference in the request channel and in the response channel is taken into account
Keywords: об'єкт повітрянний; ідентифікаційна система спостереження